Dielectric ceramic-ferrite composite substrate and preparation method thereof

By introducing a transition layer material with a thermal expansion coefficient between the dielectric ceramic-feltite composite substrate, combined with 3D printing technology, the cracks and cracking problems caused by mismatch of thermal expansion coefficients during the sintering process of the composite substrate are solved, and the pass rate is improved and efficient mass production is achieved.

CN119659116APending Publication Date: 2025-03-21CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the sintering process, due to the mismatch of thermal expansion coefficients of the dielectric ceramic-ferrite composite substrate, the composite substrate has problems such as cracks and cracks, which reduces the pass rate.

Method used

The transition layer material is introduced between the dielectric ceramic material and the ferrite material. The thermal expansion coefficient of the transition layer material is between the dielectric ceramic and the ferrite. It is cured layer by layer through 3D printing technology to reduce the sealing stress.

Benefits of technology

It effectively solves the problem of cracking of composite substrates, improves the pass rate of composite substrates, and achieves high-precision and low-cost mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119659116A_ABST
    Figure CN119659116A_ABST
Patent Text Reader

Abstract

The invention relates to a dielectric ceramic-ferrite composite substrate and a preparation method thereof, the dielectric ceramic-ferrite composite substrate comprises a dielectric ceramic material, a ferrite material and a transition layer material, and the transition layer material is arranged between the dielectric ceramic material and the ferrite material; and the thermal expansion coefficient of the transition layer material is between the thermal expansion coefficient of the dielectric ceramic material and the thermal expansion coefficient of the ferrite material. The invention designs a composite ceramic integrated preparation method according to the complex processing technology of the composite substrate, and designs a transition layer material with the thermal expansion coefficient between the ferrite substrate and the dielectric ceramic substrate according to the difference and large difference between the thermal expansion coefficients of the ferrite substrate and the dielectric ceramic substrate. The problem of cracking of the composite substrate caused by stress can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-performance ceramics for the electronics industry, and in particular to a dielectric ceramic-ferrite composite substrate and a preparation method thereof. Background Art

[0002] At present, electronic information and communication technology are developing rapidly, and the requirements for miniaturization, lightweight and integration of electronic devices are getting higher and higher. Ferrite has high magnetic properties and dielectric properties as well as high resistivity. Ferrite is currently a hot spot in the research of ceramic dielectric multifunctional materials. Dielectric ceramics have good dielectric properties and are suitable for manufacturing a variety of microwave components, which can meet the requirements of circuit miniaturization, integration, high reliability and low cost. Dielectric ceramic-ferrite integrated composite materials can effectively improve the overall dielectric constant and reduce the size of the device in circulators and isolators for 5G communications.

[0003] At present, the preparation of dielectric ceramic-ferrite integrated composite materials is mostly through high-temperature co-sintering of dielectric ceramic and ferrite. During the sintering and cold processing, due to the large difference in thermal expansion coefficients between the dielectric ceramic substrate and the ferrite, stress is generated during the sintering process. Due to the stress mismatch, cracks and fissures appear in the composite substrate, resulting in a low pass rate. Summary of the invention

[0004] The main purpose of the present invention is to provide a dielectric ceramic-ferrite composite substrate which effectively solves the problem of composite substrate cracking.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A dielectric ceramic-ferrite composite substrate comprises a dielectric ceramic material, a ferrite material and a transition layer material, wherein the transition layer material is placed between the dielectric ceramic material and the ferrite material; and the thermal expansion coefficient of the transition layer material is between that of the dielectric ceramic material and the ferrite material.

[0007] The present invention also provides a method for preparing a dielectric ceramic-ferrite composite substrate, comprising the following steps:

[0008] A dielectric ceramic-ferrite composite substrate comprises a dielectric ceramic material, a ferrite material and a transition layer material, wherein the transition layer material is placed between the dielectric ceramic material and the ferrite material; and the thermal expansion coefficient of the transition layer material is between that of the dielectric ceramic material and the ferrite material.

[0009] The transition layer material includes the following raw materials in weight percentage: Bi2O3 30-40%, B2O3 20-30%, SiO2 5-10%, ZnO 2-8%, MgO 5-10%, Fe2O3 2-8%, CaO 3-5%, Mn2CO3 2-4%,

[0010] The thermal expansion coefficient of the transition layer material is 9.5-10.5×10 -6 / ℃.

[0011] The present invention also provides a method for preparing a dielectric ceramic-ferrite composite substrate, comprising the following steps:

[0012] (1) preparing a photocuring liquid and a cleaning agent, wherein the photocuring liquid includes a dielectric ceramic photocuring liquid, a ferrite photocuring liquid and a transition layer photocuring liquid;

[0013] (2) Digital design and modeling based on the required structure of the composite ceramic substrate;

[0014] (3) Setting the printing parameters of the 3D printing device;

[0015] (4) First, cure the ferrite light-curing liquid and clean the pipe with a cleaning agent;

[0016] (5) The transition layer light curing liquid is then cured and the pipeline is cleaned with a cleaning agent;

[0017] (6) Finally, the dielectric ceramic light-curing liquid is cured and the pipeline is cleaned with a cleaning agent;

[0018] (7) repeating steps (4), (5) and (6) until the desired height is reached and stopping, thereby completing the preparation of the composite ceramic green body;

[0019] (8) drying, thermally degreasing and sintering the composite ceramic green body to produce a composite dielectric ceramic;

[0020] (9) The sintered composite dielectric ceramic is sliced, surface ground and polished to obtain a dielectric ceramic-ferrite composite substrate.

[0021] The photocurable liquid is composed of a base material and a photosensitive resin;

[0022] The photosensitive resin includes a dispersant, a plasticizer, a binder, a photoinitiator and a resin;

[0023] The dispersant is one of dispersant BYK111, dispersant BYK110 and dispersant BYK180;

[0024] The plasticizer is polyethylene glycol;

[0025] The adhesive is carrageenan;

[0026] The photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator TPO), 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone (photoinitiator 907) or 1-hydroxycyclohexylphenyl ketone (photoinitiator 184);

[0027] The resin is selected from at least one of monofunctional monomers acryloylmorpholine, trifunctional monomers trimethylolpropane triacrylate, isoacrylate and ethoxy pentaerythritol tetraacrylate;

[0028] The matrix material is ferrite ceramic powder, transition layer material and dielectric ceramic powder.

[0029] The photosensitive resin is composed of the following raw materials in weight percentage: 70-80% of resin, 2-10% of adhesive, 4-12% of photoinitiator, 1-4% of dispersant and 2-5% of plasticizer.

[0030] The preparation steps of the photocurable liquid are:

[0031] The photocurable liquid raw materials are weighed according to the weight percentage, mixed evenly, and then ball-milled. The ball-milling speed is 150 rpm-200 rpm, and the ball-milling time is 3 h-6 h;

[0032] The ball-milled mixture is vacuum defoamed to obtain a photocurable liquid.

[0033] The cleaning agent is selected from at least one of deionized water, a surfactant, petroleum ether and anhydrous ethanol;

[0034] The surfactant is selected from at least one of isopropanolamide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and fatty alcohol ether carboxylate.

[0035] The ferrite light-curing liquid is composed of the following raw materials in weight percentage: 75-90% ferrite ceramic powder and 10-25% photosensitive resin;

[0036] The ferrite ceramic powder comprises 90-95% by mass of a ferrite ceramic main component and 5%-10% by mass of a first flux, wherein the ferrite ceramic main component is one of Ni-Zn-O, Ni-Fe-O and Ni-Co-O systems, the first flux is one or two of Bi2O3, B2O3, SiO2 and ZnO, and the thermal expansion coefficient of the ferrite material is 8.5×10 -6 / ℃-9.5×10 -6 / ℃;

[0037] The transition layer photocurable liquid is composed of the following raw materials in weight percentage: 75-90% of transition layer material and 10-25% of photosensitive resin;

[0038] The transition layer material is composed of some raw materials contained in dielectric ceramics and ferrite ceramics and sintering aids, including the following raw materials in weight percentage: Bi2O3 30-40%, B2O3 20-30%, SiO2 5-10%, ZnO 2-8%, MgO 5-10%, Fe2O3 2-8%, CaO 3-5%, Mn2CO3 2-4%, and the thermal expansion coefficient of the transition layer material is 9.5-10.5×10 -6 / ℃;

[0039] The dielectric ceramic light-curing liquid is composed of the following raw materials in weight percentage: 75-90% dielectric ceramic powder and 10-25% photosensitive resin;

[0040] The dielectric ceramic powder comprises a ceramic main component with a mass percentage of 93%-96% and a second flux with a mass percentage of 4%-7%, wherein the ceramic main component is one or two of MgTiO3, CaTiO3 and Mg2TiO4, and the second flux is two or more of Li2O, B2O3, ZnO and CuO. The thermal expansion coefficient of the dielectric ceramic thermal material is 10.5×10 -6 / ℃-11.5×10 -6 / ℃.

[0041] The printing parameters of the 3D printing device are set as follows: 3D printing is layer-by-layer curing, the slice thickness is 40-60 μm, the ultraviolet light wavelength is 350nm-405nm, and the light power is 45-65mW / cm 2 , exposure time is 15-26s.

[0042] The drying temperature of the composite ceramic green body is 90-100° C., and the drying time is 4-8 hours; the sintering temperature is 1200-1360° C., and the sintering time is 120 minutes;

[0043] The thermal degreasing is carried out in an air atmosphere, and the temperature control program of the degreasing is:

[0044]

[0045] Among them, T max 850-950℃;

[0046] The heating conditions for sintering are:

[0047]

[0048] The Tmax 1200℃-1360℃;

[0049] The height of the composite ceramic green body is 5-7 cm;

[0050] The surface roughness of the composite dielectric ceramic after polishing is 7nm-10nm.

[0051] The present invention designs a composite ceramic integrated preparation method based on the complex processing technology of the composite substrate, and designs a transition layer material with a thermal expansion coefficient between the ferrite and dielectric ceramic substrates based on the different and large difference in thermal expansion coefficients between ferrite and dielectric ceramic substrates, which can effectively solve the problem of composite substrate cracking caused by stress. It has the following advantages:

[0052] 1. Use 3D printing technology to prepare composite ceramics, which has high precision, easy control and saves manpower;

[0053] 2. Optimize the formula of transition layer materials to meet the requirement that the expansion coefficient is between the dielectric ceramic substrate and ferrite, reduce the sealing stress, and increase the qualified rate of the composite substrate;

[0054] 3. The present invention can be mass-produced and the processing cycle can be shortened.

[0055] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a schematic structural diagram of a dielectric ceramic-ferrite composite substrate provided by an embodiment of the present invention;

[0057] Figure 2 It is a composite substrate processing flow chart of a dielectric ceramic-ferrite composite substrate provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0058] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0059] See also Figure 1A dielectric ceramic-ferrite composite substrate includes a dielectric ceramic material 1, a ferrite material 2 and a transition layer material 3, wherein the transition layer material 3 is placed between the dielectric ceramic material 1 and the ferrite material 2; and the thermal expansion coefficient of the transition layer material 3 is between that of the dielectric ceramic material 1 and the ferrite material 2.

[0060] like Figure 2 As shown, a method for preparing a dielectric ceramic-ferrite composite substrate comprises the following steps:

[0061] S101, prepare light curing liquid:

[0062] The photocurable liquid includes dielectric ceramic photocurable liquid, ferrite photocurable liquid and transition layer photocurable liquid;

[0063] S102, Digital Design and Modeling:

[0064] Digital design and modeling according to the required structure of the composite ceramic substrate;

[0065] S103, setting printing parameters

[0066] The printing parameters of the 3D printing equipment are set as 3D printing for layer-by-layer curing, slice thickness of 40-60μm, that is, the thickness of each print, UV wavelength of 350-405nm, and light power of 45-65mW / cm 2 , exposure time is 15-26s.

[0067] S104, printing light curing liquid 1:

[0068] First, the ferrite light-curing liquid is printed, and then the ferrite light-curing liquid is cured;

[0069] S105, cleaning:

[0070] Clean the pipes with cleaning agent;

[0071] S106, printing light curing liquid 2:

[0072] Then print the transition layer light curing liquid: solidify the transition layer light curing liquid;

[0073] S107, cleaning:

[0074] Clean the pipe again with cleaning agent;

[0075] S108, printing light curing liquid 3:

[0076] Finally, the medium ceramic light-curing liquid is printed and the medium ceramic light-curing liquid is cured;

[0077] S109, Cleaning:

[0078] Clean the pipes with cleaning agent;

[0079] Repeat steps S104-S109: stop printing when the required height of 6 cm is reached, and complete the preparation of the composite ceramic green body;

[0080] S1010, Dry:

[0081] Drying the composite ceramic green body at 90-100° C. for 4-8 hours;

[0082] S1011, debinding sintering:

[0083] The dried composite ceramic green body is degreased and sintered according to certain sintering conditions;

[0084] S1012, slices:

[0085] The sintered composite ceramics are sliced;

[0086] S1013, polishing:

[0087] After surface grinding and polishing, a dielectric ceramic-ferrite composite substrate with a surface roughness of 8nm was obtained.

[0088] S1014, Inspection:

[0089] Appearance inspection: Visually inspect the appearance of the composite substrate one by one to see if there are defects such as cracks, impurities, pores, etc. If there are obvious cracks, impurities in pieces, pores and other defects, it is unqualified.

[0090] The dispersant BYK111, dispersant BYK110 and dispersant BYK180 of the present invention are purchased from BYK Chemical Company of Germany.

[0091] The present invention will be further described below by means of specific embodiments:

[0092] Example 1

[0093] A method for preparing a dielectric ceramic-ferrite composite substrate comprises the following steps:

[0094] (1) Preparation of light curing liquid and cleaning agent:

[0095] a. Preparation of photosensitive resin:

[0096] Prepare the following raw materials according to weight percentage:

[0097] Dispersant BYK111 3%, polyethylene glycol 4%, carrageenan 5%, photoinitiator 819 8%, monofunctional monomer acryloylmorpholine 80%;

[0098] b. Prepare ferrite light curing liquid:

[0099] The ferrite light-curing liquid is composed of the following raw materials in weight percentage: 80% ferrite ceramic powder and 20% photosensitive resin;

[0100] The ferrite ceramic powder comprises a main component of Ni-Zn-O system ferrite ceramic and Bi2O3;

[0101] The main components of the Ni-Zn-O system ferrite ceramic account for 93% by mass, and Bi2O3 accounts for 7% by mass;

[0102] The thermal expansion coefficient of the ferrite material is 9.0×10 -6 / ℃;

[0103] The ferrite ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 180 rpm for 4 h;

[0104] The ball-milled mixture is vacuum defoamed to obtain a ferrite light-curing liquid.

[0105] c. Prepare the transition layer light curing liquid:

[0106] The transition layer photocurable liquid is composed of the following raw materials in weight percentage: 75% transition layer material and 25% photosensitive resin;

[0107] The transition layer material is composed of some raw materials contained in dielectric ceramics and ferrite ceramics and sintering aids, including the following raw materials in weight percentage: Bi2O3 38%, B2O3 25%, SiO2 8%, ZnO 6%, MgO 8%, Fe2O3 7%, CaO 4%, Mn2CO3 4%;

[0108] The thermal expansion coefficient of the transition layer material is 10.0×10 -6 / ℃;

[0109] The transition layer material and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 200 rpm for 2 h;

[0110] The ball-milled mixture is vacuum defoamed to obtain a transition layer photocurable liquid.

[0111] d. Prepare dielectric ceramic light curing liquid:

[0112] The dielectric ceramic light-curing liquid is composed of the following raw materials in weight percentage: 90% dielectric ceramic powder and 10% photosensitive resin;

[0113] The dielectric ceramic powder includes a ceramic main component and a second flux, wherein the ceramic main component is MgTiO3;

[0114] The second flux is Li2O and B2O3;

[0115] The ceramic main component MgTiO3 accounts for 95% by mass, Li2O accounts for 3% by mass, and B2O3 accounts for 2% by mass;

[0116] The thermal expansion coefficient of the dielectric ceramic thermal material is 11.0×10 -6 / ℃;

[0117] The dielectric ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 150 rpm for 2 h;

[0118] The ball-milled mixture is vacuum defoamed to obtain a dielectric ceramic photocurable liquid.

[0119] The cleaning agent is isopropyl alcohol amide;

[0120] (2) Digital design and modeling based on the required structure of the composite ceramic substrate;

[0121] (3) Setting the printing parameters of the 3D printing device;

[0122] 3D printing is layer-by-layer curing, the slice thickness is 50μm, the UV wavelength is 365nm, and the optical power is 55mW / cm 2 , the exposure time is 20s.

[0123] (4) First, print the ferrite light-curing liquid, cure the ferrite light-curing liquid, and clean the pipe with a cleaning agent;

[0124] (5) Printing a transition layer of light-curing liquid, curing the transition layer of light-curing liquid, and cleaning the pipeline with a cleaning agent;

[0125] (6) Finally, print the dielectric ceramic photocurable liquid, solidify the dielectric ceramic photocurable liquid, and clean the pipeline with a cleaning agent;

[0126] (7) repeating steps (4), (5) and (6) until the thickness reaches 6 cm, thereby completing the preparation of the composite ceramic green body;

[0127] (8) drying the composite ceramic green body at 95° C. for 6 h; thermal debinding and sintering;

[0128] The thermal degreasing is carried out in an air atmosphere, and the temperature control program of the degreasing is shown in Table 1 below:

[0129] Table 1

[0130]

[0131] The sintering is carried out according to the heating conditions in Table 2:

[0132] Table 2

[0133]

[0134] (9) The sintered composite dielectric ceramic is sliced, surface ground and polished to obtain a dielectric ceramic-ferrite composite substrate with a surface roughness of 8 nm.

[0135] Example 2

[0136] A method for preparing a dielectric ceramic-ferrite composite substrate comprises the following steps:

[0137] (1) Preparation of light curing liquid and cleaning agent:

[0138] a. Preparation of photosensitive resin:

[0139] Prepare the following raw materials according to weight percentage:

[0140] Dispersant BYK110 2%, polyethylene glycol 5%, carrageenan 10%, photoinitiator 907 12%, trifunctional monomer trimethylolpropane triacrylate 11%, isoacrylate 10% and ethoxy pentaerythritol tetraacrylate 50%

[0141] b. Prepare ferrite light curing liquid:

[0142] The ferrite light-curing liquid is composed of the following raw materials in weight percentage: 75% ferrite ceramic powder and 25% photosensitive resin;

[0143] The ferrite ceramic powder includes a ferrite ceramic main component and a first flux, wherein the ferrite ceramic main component is a Ni-Co-O system; the first flux is SiO2 and ZnO;

[0144] The Ni-Co-O system accounts for 90% by mass, SiO2 accounts for 6% by mass, and ZnO accounts for 4% by mass;

[0145] The thermal expansion coefficient of the ferrite material is 8.5×10 -6 / ℃;

[0146] The ferrite ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 170 rpm for 5 h;

[0147] The ball-milled mixture is vacuum defoamed to obtain a ferrite light-curing liquid.

[0148] c. Prepare the transition layer light curing liquid:

[0149] The transition layer photocurable liquid is composed of the following raw materials in weight percentage: 80% of transition layer material and 20% of photosensitive resin;

[0150] The transition layer material is composed of some raw materials contained in dielectric ceramics and ferrite ceramics and sintering aids, including the following raw materials in weight percentage: Bi2O3 40%, B2O3 30%, SiO2 10%, ZnO 8%, MgO 5%, Fe2O3 2%, CaO 3%, Mn2CO3 2%;

[0151] The thermal expansion coefficient of the transition layer material is 9.5×10 -6 / ℃;

[0152] The transition layer material and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 190 rpm for 3 h;

[0153] The ball-milled mixture is vacuum defoamed to obtain a transition layer photocurable liquid.

[0154] d. Prepare dielectric ceramic light curing liquid:

[0155] The dielectric ceramic light-curing liquid is composed of the following raw materials in weight percentage: 75% dielectric ceramic powder and 25% photosensitive resin;

[0156] The dielectric ceramic powder includes a ceramic main component and a second flux, wherein the ceramic main component is MgTiO3 and CaTiO3;

[0157] The second flux is ZnO and CuO;

[0158] Among them, MgTiO3 accounts for 85% by mass, CaTiO3 accounts for 11% by mass, ZnO accounts for 2% by mass, and CuO accounts for 2% by mass;

[0159] The thermal expansion coefficient of the dielectric ceramic thermal material is 10.5×10 -6 / ℃.

[0160] The dielectric ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 150 rpm for 6 h;

[0161] The ball-milled mixture is vacuum defoamed to obtain a dielectric ceramic photocurable liquid.

[0162] The cleaning agent is isopropyl alcohol amide;

[0163] (2) Digital design and modeling based on the required structure of the composite ceramic substrate;

[0164] (3) Setting the printing parameters of the 3D printing device;

[0165] 3D printing is layer-by-layer curing, the slice thickness is 40μm, the UV wavelength is 385nm, and the optical power is 65mW / cm 2 , the exposure time is 15s.

[0166] (4) First, print the ferrite light-curing liquid, cure the ferrite light-curing liquid, and clean the pipe with a cleaning agent;

[0167] (5) Printing a transition layer of light-curing liquid, curing the transition layer of light-curing liquid, and cleaning the pipeline with a cleaning agent;

[0168] (6) Finally, print the dielectric ceramic photocurable liquid, solidify the dielectric ceramic photocurable liquid, and clean the pipeline with a cleaning agent;

[0169] (7) repeating steps (4), (5) and (6) until the thickness reaches 5 cm, thereby completing the preparation of the composite ceramic green body;

[0170] (8) drying the composite ceramic green body at 90° C. for 8 h; thermal debinding and sintering;

[0171] The thermal degreasing is carried out in an air atmosphere, and the temperature control program of the degreasing is shown in Table 1 below:

[0172] Table 1

[0173]

[0174] The sintering is carried out according to the heating conditions in Table 2:

[0175] Table 2

[0176]

[0177] (9) The sintered composite dielectric ceramic is sliced, surface ground and polished to obtain a dielectric ceramic-ferrite composite substrate with a surface roughness of 7 nm.

[0178] Example 3

[0179] A method for preparing a dielectric ceramic-ferrite composite substrate comprises the following steps:

[0180] (1) Preparation of light curing liquid and cleaning agent:

[0181] a. Preparation of photosensitive resin:

[0182] Prepare the following raw materials according to weight percentage:

[0183] Dispersant BYK180 1%, polyethylene glycol 2%, carrageenan 9%, photoinitiator TPO 11%, isoacrylate 37%, ethoxy pentaerythritol tetraacrylate 40%;

[0184] b. Prepare ferrite light curing liquid:

[0185] The ferrite light-curing liquid is composed of the following raw materials in weight percentage: 90% ferrite ceramic powder and 10% photosensitive resin;

[0186] The ferrite ceramic powder includes a ferrite ceramic main component Ni-Fe-O system and a first flux B2O3;

[0187] The Ni-Fe-O system accounts for 95% by mass, and B2O3 accounts for 5% by mass;

[0188] The thermal expansion coefficient of the ferrite material is 9.5×10 -6 / ℃;

[0189] The ferrite ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 200 rpm for 2 h;

[0190] The ball-milled mixture is vacuum defoamed to obtain a ferrite light-curing liquid.

[0191] c. Prepare the transition layer light curing liquid:

[0192] The transition layer photocurable liquid is composed of the following raw materials in weight percentage: 90% transition layer material and 10% photosensitive resin;

[0193] The transition layer material is composed of some raw materials contained in dielectric ceramics and ferrite ceramics and sintering aids, including the following raw materials in weight percentage: Bi2O3 30%, B2O3 29%, SiO2 9%, ZnO 5%, MgO 10%, Fe2O3 8%, CaO 5%, Mn2CO3 4%;

[0194] The thermal expansion coefficient of the transition layer material is 10.5×10 -6 / ℃;

[0195] The transition layer material and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 150 rpm for 2 h;

[0196] The ball-milled mixture is vacuum defoamed to obtain a transition layer photocurable liquid.

[0197] d. Prepare dielectric ceramic light curing liquid:

[0198] The dielectric ceramic light-curing liquid is composed of the following raw materials in weight percentage: 85% dielectric ceramic powder and 15% photosensitive resin;

[0199] The dielectric ceramic powder includes a ceramic main component and a second flux, wherein the ceramic main component is MgTiO3 and Mg2TiO4;

[0200] The second flux is Li2O, B2O3 and ZnO;

[0201] Among them, MgTiO3 accounts for 86% by weight, Mg2TiO4 accounts for 7% by weight, Li2O accounts for 3% by weight, B2O3 accounts for 2% by weight, and ZnO accounts for 2% by weight;

[0202] The thermal expansion coefficient of the dielectric ceramic thermal material is 11.5×10 -6 / ℃;

[0203] The dielectric ceramic powder and the photosensitive resin were weighed according to the weight percentage, mixed evenly, and then ball-milled at a ball-milling speed of 200 rpm for 6 h;

[0204] The ball-milled mixture is vacuum-defoamed to obtain a dielectric ceramic light-curing liquid;

[0205] The cleaning agent is isopropyl alcohol amide;

[0206] (2) Digital design and modeling based on the required structure of the composite ceramic substrate;

[0207] (3) Setting the printing parameters of the 3D printing device;

[0208] 3D printing is layer-by-layer curing, the slice thickness is 60μm, the UV wavelength is 405nm, and the optical power is 45mW / cm 2 , the exposure time is 26s.

[0209] (4) First, print the ferrite light-curing liquid, cure the ferrite light-curing liquid, and clean the pipe with a cleaning agent;

[0210] (5) Printing a transition layer of light-curing liquid, curing the transition layer of light-curing liquid, and cleaning the pipeline with a cleaning agent;

[0211] (6) Finally, print the dielectric ceramic photocurable liquid, solidify the dielectric ceramic photocurable liquid, and clean the pipeline with a cleaning agent;

[0212] (7) repeating steps (4), (5) and (6) until the thickness reaches 7 cm, thereby completing the preparation of the composite ceramic green body;

[0213] (8) drying the composite ceramic green body at 100° C. for 4 h; thermal debinding and sintering;

[0214] The thermal degreasing is carried out in an air atmosphere, and the temperature control program of the degreasing is shown in Table 1 below:

[0215] Table 1

[0216]

[0217] The sintering is carried out according to the heating conditions in Table 2:

[0218] Table 2

[0219]

[0220] (9) The sintered composite dielectric ceramic is sliced, surface ground and polished to obtain a dielectric ceramic-ferrite composite substrate with a surface roughness of 10 nm.

[0221] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A dielectric ceramic-ferrite composite substrate, characterized in that: It comprises dielectric ceramic material, ferrite material and transition layer material. The transition layer material is placed between the dielectric ceramic material and the ferrite material. The thermal expansion coefficient of the transition layer material is between that of the dielectric ceramic material and the ferrite material.

2. The dielectric ceramic-ferrite composite substrate according to claim 1, characterized in that: The transition layer material includes the following raw materials in weight percentage: Bi2O3 30-40%, B2O3 20-30%, SiO2 5-10%, ZnO 2-8%, MgO 5-10%, Fe2O3 2-8%, CaO 3-5%, Mn2CO3 2-4%, The thermal expansion coefficient of the transition layer material is 9.5-10.5×10 -6 / ℃.

3. A method for preparing a dielectric ceramic-ferrite composite substrate, characterized in that: The following steps are involved: (1) preparing a photocurable liquid and a cleaning agent, wherein the photocurable liquid includes a dielectric ceramic photocurable liquid, a ferrite photocurable liquid and a transition layer photocurable liquid; (2) Digital design and modeling based on the required structure of the composite ceramic substrate; (3) Setting the printing parameters of the 3D printing device; (4) First, cure the ferrite light-curing liquid and clean the pipe with a cleaning agent; (5) The transition layer light curing liquid is then cured and the pipeline is cleaned with a cleaning agent; (6) Finally, the dielectric ceramic light-curing liquid is cured and the pipeline is cleaned with a cleaning agent; (7) repeating steps (4), (5) and (6) until the desired height is reached and stopping, thereby completing the preparation of the composite ceramic green body; (8) drying, thermally degreasing and sintering the composite ceramic green body to produce a composite dielectric ceramic; (9) The sintered composite dielectric ceramic is sliced, surface ground and polished to obtain a dielectric ceramic-ferrite composite substrate.

4. The preparation method according to claim 3, characterized in that: The photocurable liquid is composed of a base material and a photosensitive resin; The photosensitive resin includes a dispersant, a plasticizer, a binder, a photoinitiator and a resin; The dispersant is one of dispersant BYK111, dispersant BYK110 and dispersant BYK180; The plasticizer is polyethylene glycol; The adhesive is carrageenan; The photoinitiator is one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator TPO), 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone (photoinitiator 907) and 1-hydroxycyclohexylphenyl ketone (photoinitiator 184); The resin is selected from at least one of monofunctional monomers acryloylmorpholine, trifunctional monomers trimethylolpropane triacrylate, isoacrylate and ethoxy pentaerythritol tetraacrylate; The matrix material is ferrite ceramic powder, transition layer material and dielectric ceramic powder.

5. The preparation method according to claim 4, characterized in that: The photosensitive resin is composed of the following raw materials in weight percentage: 70-80% resin, 2-10% adhesive, 4-12% photoinitiator, 1-4% dispersant, and 2-5% plasticizer.

6. The preparation method according to claim 5, characterized in that: The preparation steps of the photocurable liquid are: The photocurable liquid raw materials are weighed according to the weight percentage, mixed evenly, and then ball-milled. The ball-milling speed is 150 rpm-200 rpm, and the ball-milling time is 3 h-6 h; The ball-milled mixture is vacuum defoamed to obtain a photocurable liquid.

7. The preparation method according to claim 6, characterized in that: The cleaning agent is selected from at least one of deionized water, a surfactant, petroleum ether and anhydrous ethanol; The surfactant is selected from at least one of isopropanolamide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and fatty alcohol ether carboxylate.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The ferrite light-curing liquid is composed of the following raw materials in weight percentage: 75-90% ferrite ceramic powder and 10-25% photosensitive resin; The ferrite ceramic powder comprises 90-95% by mass of a ferrite ceramic main component and 5%-10% by mass of a first flux, wherein the ferrite ceramic main component is one of Ni-Zn-O, Ni-Fe-O and Ni-Co-O systems, the first flux is one or two of Bi2O3, B2O3, SiO2 and ZnO, and the thermal expansion coefficient of the ferrite material is 8.5×10 -6 / ℃-9.5×10 -6 / ℃; The transition layer photocurable liquid is composed of the following raw materials in weight percentage: 75-90% of transition layer material and 10-25% of photosensitive resin; The transition layer material is composed of some raw materials contained in dielectric ceramics and ferrite ceramics and sintering aids, including the following raw materials in weight percentage: Bi2O3 30-40%, B2O3 20-30%, SiO2 5-10%, ZnO 2-8%, MgO 5-10%, Fe2O3 2-8%, CaO 3-5%, Mn2CO3 2-4%, and the thermal expansion coefficient of the transition layer material is 9.5-10.5×10 -6 / ℃; The dielectric ceramic light-curing liquid is composed of the following raw materials in weight percentage: 75-90% dielectric ceramic powder and 10-25% photosensitive resin; The dielectric ceramic powder comprises a ceramic main component with a mass percentage of 93%-96% and a second flux with a mass percentage of 4%-7%, wherein the ceramic main component is one or two of MgTiO3, CaTiO3 and Mg2TiO4, and the second flux is two or more of Li2O, B2O3, ZnO and CuO. The thermal expansion coefficient of the dielectric ceramic thermal material is 10.5×10 -6 / ℃-11.5×10 -6 / ℃.

9. The preparation method according to claim 8, characterized in that: The printing parameters of the 3D printing device are set as follows: 3D printing is layer-by-layer curing, the slice thickness is 40-60 μm, the ultraviolet light wavelength is 350nm-405nm, and the light power is 45-65mW / cm 2 , exposure time is 15-26s.

10. The preparation method according to claim 9, characterized in that: The drying temperature of the composite ceramic green body is 90-100° C. and the drying time is 4-8 hours; The thermal degreasing is carried out in an air atmosphere, and the temperature control program of the degreasing is: Among them, T max 850-950℃; The heating conditions for sintering are: The T max 1200℃-1360℃; The height of the composite ceramic green body is 5-7 cm; The surface roughness of the composite dielectric ceramic after polishing is 7nm-10nm.